Building Research Capacity for Impact in Applied Health Services Research Partnerships; Comment on "Experience of Health Leadership in Partnering With University-Based Researchers in Canada - A Call to "Re-imagine" Research" - Jo Cooke (Kerman University of Medical Sciences, 2021)
Bowen and colleagues ask us to re-imagine how to conduct research in academic-practice partnerships, and to develop capacity in the applied research and health workforce to do this. This commentary reinforces their messages, and describes a framework of research capacity development for impact (RCDi) which emphasizes active and continuous experiential learning within research partnerships. The RCDi framework includes the need to focus on multiple levels in the collaboration architecture, and describes principles of working that aims to increase impact on services, and learning opportunities for all partners.